Master of the game - Sheldon, Sidney (Grand Central Publishing, 2017)
Kate Blackwell is the symbol of success, a beautiful woman who parlayed her inheritance into an international conglomerate. Winner of a unique position among the wealthy and world-renowned, she's also a survivor as indomitable as her father, who returned from the edge of death to wrench a fortune in diamonds from the hard South African soil. Now, celebrating her ninetieth birthday, Kate surveys the family she has manipulated, dominated, and loved: the fair and the grotesque, the mad and the mild, the good and the evil.--